Potency and Sterility of Fortified Tobramycin, Fortified Vancomycin, and Moxifloxacin at 4, 24, and 35°C for 14 Days. Issue 1 (January 2016) - Montes, Jorge A.; Johnson, Daniel; Jorgensen, James; McElmeel, M. Leticia; Fulcher, Letitia C.; Kiel, Jeffrey W.
Abstract : Purpose: To assess the potency and sterility of ophthalmic antibiotic drops commonly used in the treatment of bacterial keratitis. Methods: This was a basic investigation. Three drugs were tested: fortified vancomycin 25 mg/mL, fortified tobramycin 14 mg/mL, and moxifloxacin 5 mg/mL. A bottle of each was stored separately at 4, 24, and 35°C, with the potency determined by microbiological assay at 0, 7, and 14 days. Differences in potency were assessed by 2-way analysis of variance followed by a 1-way repeated-measures analysis of variance with Bonferroni post hoc testing as warranted. Sterility of drugs when handled by patients for varying periods was confirmed by culturing samples on MacConkey and sheep blood agars. Results: The concentration of fortified tobramycin and moxifloxacin remained constant over 14 days at the 3 tested temperatures. The concentration of fortified vancomycin remained constant at 4°C, but it declined by 38% ± 1% ( P = 0.001) at 24°C on day 14 and by 48% ± 1% ( P = 0.001) and 78% ± 3% ( P = 0.0009) at 35°C on days 7 and 14, respectively. A total of 49 drops (mean, 7.3 days; range, 1–18 days) were tested for sterility, and all were negative for microbial contamination. Conclusions: All 3 drugs remained potent at 4°C for up to 14 days. Fortified tobramycin and moxifloxacin also maintained potency for 14 days at 24 and 35°C. In contrast, fortified vancomycin lost its potency by day 14 at 24°C and by day 7 at 35°C. All in-use antibiotic drops tested were sterile. The results indicate that patients should be cautioned to store vancomycin under refrigerator or at least under cool conditions.